2015
DOI: 10.1371/journal.pone.0136751
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Acceleration to Code for Animal Behaviours; A Case Study in Free-Ranging Eurasian Beavers Castor fiber

Abstract: Recent technological innovations have led to the development of miniature, accelerometer-containing electronic loggers which can be attached to free-living animals. Accelerometers provide information on both body posture and dynamism which can be used as descriptors to define behaviour. We deployed tri-axial accelerometer loggers on 12 free-ranging Eurasian beavers Castor fiber in the county of Telemark, Norway, and on four captive beavers (two Eurasian beavers and two North American beavers C. canadensis) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 79 publications
1
94
0
Order By: Relevance
“…Higher mean ODBA levels in the middle of the night suggest that this is the peak activity time for beavers. The mean ODBA value for standing (or being inactive) is 0.06 g (σ = 0.02 g) (Graf et al 2015) and none of our mean ODBA values was below 0.1 g, which suggests that the animals were active during all seven nights after the tagging event.…”
Section: Reduced Activity Level (Mean Odba)mentioning
confidence: 67%
See 3 more Smart Citations
“…Higher mean ODBA levels in the middle of the night suggest that this is the peak activity time for beavers. The mean ODBA value for standing (or being inactive) is 0.06 g (σ = 0.02 g) (Graf et al 2015) and none of our mean ODBA values was below 0.1 g, which suggests that the animals were active during all seven nights after the tagging event.…”
Section: Reduced Activity Level (Mean Odba)mentioning
confidence: 67%
“…Mean ODBA at 8 Hz was calculated by summing up the dynamic acceleration logged in all three axes ) and averaged over 15 min to investigate movement-based activity levels for each individual. The beavers' principal activity periods were determined visually by identifying movement patterns indicating when the beavers left their lodges (indicated by the first dive in the evening) and returned to the lodges again (the last dive in the morning followed by a grooming session; for information on behavioural identification using accelerometry, see Graf et al (2015)). The first night was excluded from this analysis since we captured beavers that night and thus did not have a full principal activity period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VeDBA and ODBA values may also provide information about energy expenditure [e.g., Qasem et al, 2012;Jeanniard-du-Dot et al, 2017]. Accelerometer data can be used to derive daily activity budgets [e.g., when an animal moves; Yoda et al, 1999;Lagarde et al, 2008;Grü newä lder et al, 2012;Williams et al, 2014] and, if accelerometer and viewer-observed behavioural data are collected simultaneously, accelerometer data can also be used to characterise behaviours (e.g., walking, running, and leaping) [Sakamoto et al, 2009;Nathan et al, 2012;Graf et al, 2015] and to estimate the energy expenditure associated with different behaviours [Wilson et al, 2006;Qasem et al, 2012;Jeanniard-du-Dot et al, 2017]. Until now, accelerometers have primarily been deployed on large-bodied species [ Fig.…”
Section: Introductionmentioning
confidence: 99%